Providing Space to the Marginalized: Bertolt Brecht’s Reception of John Gay’s The Beggar’s Opera - Isti Haryati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
The popularity of John Gay’s political satire play The Beggar’s Opera in the English literary world prompted a German writer, Bertolt Brecht, to respond to the work. The purpose of this study is to describe Bertolt Brecht's reception of Gay’s Play The Beggar’s Opera in Brecht’s Play Die Dreigroschenoper. The data sources in this study are the text of Brecht’s play entitled Die Drei Groschenoper and the text of Gay’s play The Beggar's Opera. This research is based on the theory of Reception Aesthetics by Hans Robert Jauss. The results show that Brecht’s reception was influenced by his horizon of expectations, which plays a central role in determining a writer’s reception of a work of literature. Brecht’s horizon of expectations, which is related to his Marxist view, distinguishes Brecht’s play from that by Gay. Brecht’s intention to make a play that enlightens his audience made him present a more explicit depiction of marginalized people in Die Dreigroschenoper, which was performed in the form of epic theater (episches Theater). By providing space to the marginalized, Brecht aimed to criticize capitalism which began to grow in Germany after the country’s loss in the First World War and divided the German society into two classes, resulting in various social issues. Brecht’s criticisms are different from Gay’s criticisms in shedding some light on the moral degradation in England at the time.